Comparing Traditional Instructional Methods to ChatGPT: A Comprehensive Analysis - B, Ramprakash; B, Surya Devi; G, Dr. Nithyakala; K, Bhumika; S, Avanthika (Journal of Engineering Education Transformations, 2024)
In today's educational landscape, shaped by rapid technological advancements, this study addresses the pertinent issue of inclusion of artificial intelligence (AI) in mathematics education. The focus is specifically on the utilization of ChatGPT, an AI-driven tool, to enhance the comprehension of differentiation and integration concepts among students. The contemporary educational context emphasizes the significance of AI in transforming learning experiences. However, the practical implications of AI implementation remain a subject of inquiry and exploration. This study seeks to bridge the gap between the potential of AI and its actual impact on learning outcomes. This research engages a comprehensive approach, involving both a survey and a subsequent post-test assessment. The survey phase aims to capture the viewpoints of students, regarding their preferences and experiences with traditional versus AI-driven problem-solving methods. Subsequently, the post-test evaluation seeks to measure the efficacy of ChatGPT. Participants found the AI tool particularly useful for clarifying complex concepts and providing immediate solutions. However, some students also expressed a preference for the personalized interaction and contextual explanations that human instructors offer. The findings suggest that while AI assistance has its merits, a balanced approach that integrates human expertise and AI support can potentially create a more comprehensive learning experience. Keywords—ChatGPT, Artificial Intelligence, Differentiation, Integration